Influences from SiO2 particles on optical properties of white diodes verified through computer simulation - Trang, Le Thi; Quoc Anh, Nguyen Doan (Institute of Advanced Engineering and Science, 2025)
For typical white-illumination diodes (WLEDs) based on phosphor conversion, heat consistency would be an essential element in phosphor samples, which is based on consistent discharge intensity, apex profile, as well as location as the samples function under different heat levels. With the goal of attaining desirable heat consistency, the study herein concerns the thermic mechanism in different phosphor samples singularly or dualincorporated with Ce3+ and Eu2+. Based on our acquired data, the luminescent features for the samples exhibit copious alterations when subject to different heat levels, primarily decided by phosphor bases’ crystalline formation. The assessment of the interaction among the thermic mechanism and base latticework in the samples suggest that a merger between firm crystalline formations and symmetrical locations would result in desirable thermic consistency in samples. As such, the study herein also assesses a number of formations possessing firm foundations as well as specific approaches for avoiding thermic irregularities in phosphor samples, aiming to identify reliable samples as well as approaches for augmenting heat consistency for said samples.